Mechanical, thermal, and microstructure analysis of silk- and cotton-waste-fiber-reinforced high-density polyethylene composites - KOÇAK, EMİNE DİLARA; USTA, İSMAİL; TAŞDEMİR, MÜNİR (TAYLOR & FRANCIS INC, 2008)
In this study, composite structures were produced using HDPE polymer with silk and cotton waste as reinforcement fibers in different ratios. Cotton and silk wastes were mixed in the ratios of HDPE/silk or cotton waste 100%/0%, 97%/3%, and 94%/6%. This mixture was prepared with double-screwed extruder. The tests were carried out in terms of tensile strength, % elongation, yield strength, elasticity module, izod impact strength, melt flow index (MFI), heat deflection temperature (HDT), and vicat softening temperature. Materials' thermal transitions were determined with differential scanning calorimetric (DSC) and microstructure properties with scanning electron microscope (SEM).
Keywords: cotton waste; HDPE; polymer composite; silk waste; METHACRYLAMIDE; POLYPROPYLENE; EXTRUSION; JUTE